Barriers and facilitators in the implementation of recommendations for hand eczema prevention among healthcare workers. (5th March 2015) - van der Meer, Esther W. C.; van der Gulden, Joost W. J.; van Dongen, Diana; Boot, Cécile R. L.; Anema, Johannes R.
Summary Background Evidence‐based recommendations are available for the prevention of hand eczema among healthcare workers. However, the implementation of these recommendations is not always successful. Objectives To identify barriers and facilitators in the implementation of recommendations for the prevention of hand eczema among healthcare workers alongside a randomized controlled trial. Methods A qualitative study was performed in which 19 healthcare workers were interviewed. The interview transcripts were open coded and also coded by means of a template by two researchers to identify relevant barriers and facilitators. Results Most barriers and facilitators reported for the recommendations were found at the level of the innovation (e.g. the recommendations), whereas for the guideline as a whole, multiple levels (socio‐political, organization, user, and facilities) were identified. Conclusions To enhance the implementation of recommendations for the prevention of hand eczema in a healthcare setting, having knowledge about these recommendations seems to be an important first step. In addition, maintaining the attention of the subject, testing the products beforehand and close collaboration with the infection control department might enhance implementation. Furthermore, it is important that the recommendations fit in with the work of the healthcare workers. When the implementation of the recommendations is prepared, these points should be taken into account.